2006
DOI: 10.1007/s11270-006-9135-9
|View full text |Cite
|
Sign up to set email alerts
|

Responses of restinga plant species to pollution from an iron pelletization factory

Abstract: Byrsonima sericea DC. (Malpighiaceae), Cordia verbenacea DC. (Boraginaceae) andPsidium guineense SW. (Myrtaceae) were studied in two experimental sites: a restinga forest fragment, near an iron pelletization factory (mining area) and a restinga conservation unit "Paulo César Vinha State Park". The aims were verify the effects of emissions from a pelletization factory on some anatomical and physiological parameters and on absorption and accumulation of particulate iron by the leaves. A protocol was adjusted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(37 citation statements)
references
References 18 publications
0
36
0
1
Order By: Relevance
“…Silva et al (2006) have also suggested an internal temperature increase in leaves of Cordia verbenacea and Psidium guineense growing near a pelletizing industry, as probable effect of stomata obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Silva et al (2006) have also suggested an internal temperature increase in leaves of Cordia verbenacea and Psidium guineense growing near a pelletizing industry, as probable effect of stomata obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…This observation corroborates with the data found by Silva et al, (2005) when characterizing the structural alterations caused by simulated acid rain in C. hilariana, in which the injury developed from the epidermis of the abaxial surface of the leaf. Stomata alterations caused by the deposition of particulate matter cause a physiological disturbance (FARMER, 1993;INOUE;REISSMANN, 1994;SILVA et al, 2006;PEREIRA et al, 2009), besides acting as an entrance pathway to the pollutant causing an increase in total concentration of metallic elements in the leaf tissues (GRANTZ et al, 2003). The histological organization of C. hilariana was kept unaltered after 45 days of continuous exposure to SPM Fe , presenting little structural injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations